Effect of culture media substitutions on in vitro growth of Ipecac - Jiménez-Rivera, Alexander (2019)
The micropropagation of ipecac has been seen as an alternative to supply the need for materials from producers interested in this crop. However, the uncompetitive costs of traditional tissue culture have hampered their implementation in the production of vitroplants for growing areas. In order to evaluate different substitutions in the composition of the culture media, a comparison on plants growth in different media with substitutions in mineral salts (by hydroponic salts), vitamins (by thiamine or complex B1, B6 and B12) and gelling agent (by corn starch) was made. Significant differences (a = 0.05) between the evaluated growth characteristics (shoots number, shoots length, leaves number and dry weight) were observed. A multivariate analysis showed a relationship between culture media with hydroponic salts substitution, with vitamins (B1, B6 and B12) substitution and the control media (MS); which influenced the shoots length and the leaves number. On the other hand, the media with corn starch substitution affected the shoots number and the dry weight. This last variable was also influenced by the Low Cost media (substitution of the three components). Of all treatments evaluated, the Thiamine substitution media was the one that presented the lowest yields; while the Low Cost media shows the highest according to Hotelling - Bonferroni Test. The cost analysis performed showed significant savings (up to 59%) between the Low Cost and the control treatment (MS media).